Peroxisome proliferator-activated receptors and thiazolidinediones in diabetic nephropathy - Soni, Navneet O.; Pawar, Saroja V.; Kale, Sheetal; Mane, Uday A.; Bhosale, Pravin U.; Phandhare, Komal; Bhosale, Priya R.; Patil, Smitha A. (International Journal of Basic & Clinical Pharmacology, 2019)
Diabetic nephropathy is global problem with several drugs into trial without much success the current article highlights the role of thiazolidinedione’s in diabetic nephropathy by scrutinizing and reconnoitring the cellular and intracellular mechanism and shielding action and the role of peroxisome proliferator-activated gamma receptors (PPARγ) receptors. Not only anti-diabetic action but renal protective effect with evidence based study has been highlighted. PPAR γ-is versatile target having numerous benefits and mainly preventing fibrosis in diabetic experimental model and some clinical case report yet, the benefits are not up to mark, since renal failure itself causes volume expansion and the thiazolidinedione’s (TZDs) also preserve salt and water and lead to congestive heart failure which constraints its clinical application. Dual activators and balaglitazone selective PPAR modulator are having upcoming potential for treatment of diabetic nephropathy. Further detail investigation on such drug is needed to explore. However adverse effect like heart failure, osteoporosis and volume expansion effect over-rides the beneficial effect thus limiting its clinical use of currently available TZDs.